1988
DOI: 10.1111/j.1600-0528.1988.tb00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary mercury levels and early changes in kidney function in dentists and dental assistants

Abstract: Mercury exposure and renal function parameters were examined in 68 dentists and 64 dental assistants. The levels of mercury in urine were low: only three individuals exceeded 20 micrograms/l. Increased excretion of urinary proteins and increased activity of urinary enzymes were observed. This enhanced prevalence of renal function changes appeared not to be related to the mercury urine level, age, sex, or smoking and drinking habits. Only for men was a positive relation between the level of mercury in urine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Such a reaction may result in alburninuria (22,49,50,52) and has been reported to be more prevalent in dentists and dental assistants, although not correlated with their U-Hg (47). Similar findings were also made in this study, and microalbuminuria was present in six of the patients preexperimentally.…”
Section: Discussionsupporting
confidence: 90%
“…Such a reaction may result in alburninuria (22,49,50,52) and has been reported to be more prevalent in dentists and dental assistants, although not correlated with their U-Hg (47). Similar findings were also made in this study, and microalbuminuria was present in six of the patients preexperimentally.…”
Section: Discussionsupporting
confidence: 90%
“…31 In our study, dentists were significantly more likely than control subjects to report that they had suffered from and received treatment for a kidney disorder, but there was no observed relationship between levels of urinary mercury and reporting of kidney disorders. Vershoor et al 18 similarly reported a relatively high percentage of dental staff exhibiting renal dysfunction but found no significant relationship between urinary mercury levels and kidney disorders. These authors suggested that other potential nephrotoxic agents used in dental practice, including antibiotics, local anaesthetics or composite resins, might be responsible for the observed increase in protein excretion.…”
Section: Biological Measurementsmentioning
confidence: 93%
“…Of the dentists who answered the question, 55.4% reported that they used an amalgamator in the surgery, 36.1% used single-use capsules and 8.4% used both. Of those respondents who used an amalgamator, 18.1% indicated that they themselves filled it. Forty-five per cent of the respondent dentists used encapsulated amalgam, with the results indicating the mean time that they had used capsules was 5.0 years, with a minimum of 1 month and a maximum of 32 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 These reductions are likely to have been the result of mercury screening programmes, the use of automated methods of amalgam preparation and improvements in mercury hygiene in dental surgeries. [13][14][15][16] However, several studies have shown that chronic exposure to low concentrations of mercury-such as those experienced by dentists-may have an effect on psychological performance. 9 10 17-19 In a pilot study we established the suitability of a computerised package of psychomotor tests to determine possible low level effects of mercury on an exposed population.…”
mentioning
confidence: 99%